ANALISIS PENGARUH INFORMASI PRODUK, HARGA, DAN DISKON TERHADAP KEGUNAAN PENGGUNA DALAM UPAYA MENDORONG MINAT BELI ONLINE DI TRAVELOKA.COM - Chairani, Hijri; Nugroho, Arissetyanto (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2022)
This study aims to examine and analyze the relationship between product variables, prices and discounts on user usability in an effort to encourage online buying interest at Traveloka.com. The object of this research is consumers who have bought tickets on the Traveloka.com website as a media tool in ordering hotel, flight, and entertainment tickets. The sampling technique used purposive sampling technique with a sample of 90 respondents. The data analysis technique used in this research is descriptive analysis, validity analysis, reliability analysis, multiple linear regression analysis and the coefficient of determination (R2) with the application of SPSS 20.0 analysis. The results showed that there has no positive and no significant influence on the product variable and the discount variable, while the price variable had a no positive and significant effect on the usability of users in an effort to encourage online buying interest at Traveloka.com